Impact of Health Education on Hygiene Practices Among Artisans in Warri South Local Government Area - Oyibo, Rita Uzezi; Omuvie, Ujiro; Ogbede, Oritsematsosan Marian (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
Artisans in Warri South Local Government Area of Delta State, Nigeria, face considerable health risks due to poor hygiene practices in their work environments. Despite their critical role in the local economy, these workers often lack access to effective health education, exacerbating their vulnerability to health issues and posing broader public health risks. This study investigates the impact of health education on the hygiene behaviors of artisans in Warri South, aiming to enhance understanding of how educational interventions can improve hygiene practices and health outcomes. The study employed a descriptive survey and quasi-experimental designs to assess the current level of hygiene awareness and practices among artisans, evaluate the influence of health education on their hygiene behaviors, and identify barriers to effective education. A sample of 150 artisans, randomly selected from five major areas within Warri South, participated in the study. Data were collected using a structured questionnaire with a 4-point Likert scale, and analyzed through descriptive and inferential statistics. Findings revealed that health education significantly improved artisans' hygiene knowledge, practices, and attitudes. Specifically, health education interventions led to enhanced awareness, better adherence to hygiene practices, and positive changes in health attitudes. However, barriers such as limited access to resources and resistance to change were identified as challenges to effective health education. The study concludes that targeted health education programs are effective in improving hygiene behaviors among artisans, contributing to better health outcomes and reduced disease prevalence. Recommendations were made included amongst others that government health agencies should develop and implement more accessible and targeted health education programs for artisans; Artisan unions should collaborate with public health organizations to organize regular hygiene training and workshops.